The red pyramid : the graphic novel - Collar, Orpheus; Riordan, Rick. (New York : Disney/Hyperion Books, 2012)
A graphic novel adaptation of "The Red Pyramid" in which brilliant Egyptologist Dr. Julius Kane accidentally unleashes the Egyptian god Set, who banishes the doctor to oblivion and forces his two children to embark on a dangerous journey, bringing them closer to the truth about their family and its links to a secret order that has existed since the time of the pharaohs.
"Adapted from the novel The Kane Chronicles, Book One: The Red Pyramid"--Colophon.
4.3
5-8
Keywords: Riordan, Rick. -- Adaptations; Brothers and sisters -- Comic books, strips, etc. -- Juvenile fiction; Seth (Egyptian deity) -- Comic books, strips, etc. -- Juvenile fiction; Voyages and travels -- Comic books, strips, etc. -- Juvenile fiction; Magic -- Comic books, strips, etc. -- Juvenile fiction; Secrecy -- Comic books, strips, etc. -- Juvenile fiction; Mythology, Egyptian; Riordan, Rick. -- Adaptations; Brothers and sisters -- Fiction; Seth (Egyptian deity) -- Fiction; Voyages and travels -- Fiction; Magic -- Fiction; Secrets -- Fiction; Mythology, Egyptian; Fantasy; Cartoons and comics; Riordan, Rick. -- Adaptations; Siblings -- Comic books, strips, etc. -- Fiction; Seth (Egyptian deity) -- Comic books, strips, etc. -- Fiction; Voyages and travels -- Comic books, strips, etc. -- Fiction; Magic -- Comic books, strips, etc. -- Fiction; Secrecy -- Comic books, strips, etc. -- Fiction; Egyptian mythology; Fantasy graphic novels; Comic books, strips, etc; Graphic novels; Fantasy comic books, strips, etc; Graphic novels